An overview of clinical cerebral microdialysis in acute brain injury - Stovell, Matthew G.; Helmy, Adel; Thelin, Eric P.; Jalloh, Ibrahim; Hutchinson, Peter J.; Carpenter, Keri L. H. (Frontiers in Neurology, 2023)
Cerebral microdialysis may be used in patients with severe brain injury to monitor patients’ cerebral physiology. In this article we provide a concise synopsis with illustrations and original images of catheter types, their structure, and how they function. Where and how catheters are inserted, their identification on imaging modalities (CT and MRI), together with the roles of glucose, lactate/pyruvate ratio, glutamate, glycerol and urea are summarised in acute brain injury. The research applications of microdialysis including pharmacokinetic studies, retromicrodialysis, and its use as a biomarker for efficacy of potential therapies are outlined. Finally, we explore limitations and pitfalls of the technique, as well as potential improvements and future work that is needed to progress and expand the use of this technology.